Depending on HPLC and PCR, detection of aflatoxin B1 extracted from Aspergillus flavus strains and it’s cytotoxic effect on AFB treated-hematopoietic stem cells obtained from human umbilical cord - Al-Ouqaili, Dr. Mushtak Talib S. (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Aflatoxin B1 (AFB1) is a carcinogenic metabolite produced by Aspergillus falvus which cause several diseases in humans. This study aimed to determinate the role of polymerase chain reaction (PCR) and high-performance liquid chromatography (HPLC) techniques in discrimination between aflatoxigenic and non‑aflatoxigenic producer isolates of A. flavus and molecular expression for aflatoxin encoding genes (aflM ver-1, aflD, and aflR). Furthermore, to assess the cytotoxic effect of AFB on isolated hematopoietic stem cells (HSCs) obtained from the human umbilical cord. Materials and Methods: The extracted aflatoxin was detected by HPLC. Fungal DNA was extracted and submitted to PCR for amplifying AFB encoding genes (nor1 aflD, aflM, and aflR). The collection of umbilical cord blood samples was accomplished using the system close method. CD34 were used for immunophenotypic analysis of HSC which were obtained using buffy coat method. An experimental study was conducted in vitro to assess the cytotoxicity effects of AFB with certain concentrations on the viability of AFB treated-HSC. Results: Out of 15 A. flavus, the genes (AflR, nor1 aflD) were founded in 11 (73%) of A. flavus strains, while the (ver aflM) was appeared in 10 (67%) of strains. HPLC technique had been detected efficiently AFB1-producing isolates in 10 (66.7%) out of 15 isolates of A. flavus with rates ranged from 0.78 to 45.03 ppm. It was yielded that the inhibition rate of isolated HSC was increased seriously with an increase of aflatoxins concentration leading to decrease in viability of AFB-treated cells. Conclusions: Aflatoxin production was directly associated with the appearance and expression of genes (aflM ver-1, aflD, and aflR) by PCR. Furthermore, HPLC is a superior technique in identifying and analyzing aflatoxin with high sensitivity and accuracy. Further, in a cytotoxicity assay, whenever the aflatoxin concentration was high, the rate of HSC growth inhibition increases and viability of AFB-treated cells decreased.